2021
DOI: 10.52131/pjhss.2021.0901.0109
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of English Writing Anxiety among Pakistani ESL Students: Perceptions of Teachers and Students

Abstract: English language writing skills play a significant role in academic and professional lives in the ESL context. Anxiety can have debilitating effects on learning English language listening, reading, speaking and writing skills. The objective of the current study was to explore the causes of writing anxiety in Pakistani undergraduate ESL students. The data for this study were collected from Pakistani ESL students and English language teachers in Karachi with asample that had both public and private-sector repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Among them, "technical issues", "lecturer", "time management", "insufficient knowledge in English", "distraction due to the online environment", and "lack of sufficient writing skills", were reported as the most Open Journal of Modern Linguistics frequent ones, followed by "keeping the camera on", "preparation for class or assignments", "linguistics difficulties", "fear of peer evaluation", and "low level of self-confidence" were mentioned as the least frequent ones amongst the students. Further, it is worth noting that the results of the current study with regard to the sources of writing anxiety are marginally consistent with previously conducted researches by Rezaei and Jafari (2014), Wahyuni and Umam (2017), Wahyuni et al (2019), Elif and Yayli (2019), Rabadi and Rabadi (2020), Syarifudin (2020), andFareed et al (2021). These studies have identified items such as, "poor linguistic knowledge", "lack of topical knowledge", "fear of tests", "fear of teacher's negative feedback", and "insufficient writing practice" which are relatively identical to the current study.…”
Section: Sources Of Writing Anxietysupporting
confidence: 92%
“…Among them, "technical issues", "lecturer", "time management", "insufficient knowledge in English", "distraction due to the online environment", and "lack of sufficient writing skills", were reported as the most Open Journal of Modern Linguistics frequent ones, followed by "keeping the camera on", "preparation for class or assignments", "linguistics difficulties", "fear of peer evaluation", and "low level of self-confidence" were mentioned as the least frequent ones amongst the students. Further, it is worth noting that the results of the current study with regard to the sources of writing anxiety are marginally consistent with previously conducted researches by Rezaei and Jafari (2014), Wahyuni and Umam (2017), Wahyuni et al (2019), Elif and Yayli (2019), Rabadi and Rabadi (2020), Syarifudin (2020), andFareed et al (2021). These studies have identified items such as, "poor linguistic knowledge", "lack of topical knowledge", "fear of tests", "fear of teacher's negative feedback", and "insufficient writing practice" which are relatively identical to the current study.…”
Section: Sources Of Writing Anxietysupporting
confidence: 92%
“…The present study on the concept of WA is like a ground-breaking in the context of Khyber Pakhtoon Khwa. So far as the causes of SLWA are concerned, many researchers are convinced that for a deeper understanding of the issue, more studies should be carried out in this respect by using both qualitative and quantitative methods (Rezaei and Jafari, 2014;Fareed, Khan and Akhtar (2021). Thus, the mixed method design of the present study makes up its rationale by filling the aforementioned gap.…”
Section: Research Gap For Present Studymentioning
confidence: 95%
“…While a lot of research works can be found on SLWA in other countries, this area comparatively caught less attention from Pakistani scholars; only a few recognized studies on the subject are available. In the Pakistani context, the quantitative study by Younus et al (2014) to explore the factors responsible for SLWA was followed by Fareed, Khan and Akhtar (2021) and Sloangi, Memon and Lohar (2021), which were purely qualitative and quantitative in nature respectively. Their findings suggested further studies for a deeper understanding of the topic through both qualitative and quantitative methods.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, arguments and debates have emerged regarding Urdu and English as MOIs, although barely 6.8% of Pakistani society uses Urdu (Asif et al., 2020; Fareed & Ashraf, 2019). As a result, the government has started establishing schools using both Urdu and English, single‐language schools, and schools using local languages (Bushra, 2017, Pathan et al., 2018, Rahman, 1997, 2020), with no officially documented policy regarding language use (Fareed & Ashraf, 2019; Mahboob, 2002), which creates confusion among parents (Birdsall et al., 2005; Channa et al., 2016). The Annual Status of Education Report (ASER) demonstrated that the majority of government schools prefer to adopt Urdu as the MOI (ASER, 2015), which shows that Urdu as the MOI won enough hearts to overcome politics (Rahman, 1997).…”
Section: Research Contextmentioning
confidence: 99%